Is Self-Transcendence Philanthropic? Graded Response Model Approach - Ros, Bandos; Kaneko, Shinji (Frontiers in Psychology, 2022)
This study reveals that strong feelings of altruism were found to be statistically significant in explaining prosocial and pro-environmental behaviors. However, this was not the case for the latent trait biosphere in explaining pro-environmental behavior (e.g., past volunteering in clean-up activities). Regardless of whether they are overseas graduates or not, subjects in this study, are more altruistic than biospheric. Using the Graded Response Model (GRM) approach, the study found that the biosphere and altruism are obviously independent from each other and merging them into one dimension, in this instance referred to as ‘self-transcendence’, makes the construct less reliable. That is why this study in consistence with previous studies could not detect statistically the effect of self-transcendence as it effects both the past volunteering in environmental affairs and the past volunteering in social welfares.